Preparation And Characterization Of Waterborne Acrylic Latex Polymers Pressure-Sensitive Adhesives - Yew, Fang Wey (2011)
Acrylic pressure-sensitive adhesives obtained by emulsion polymerization are environmental friendly adhesives. The monomers chosen were butyl-acrylate, acrylic acid, 2-ethylhexyl acrylate, methyl methacrylate, and 2-hydroxyethyl acrylate. The effect of varied monomer composition on adhesive performance is studied. The particle sizes of adhesives were measured by using CILAS 1180 Laser Particle Size Analyzer. ATR-FTIR spectroscopy was used to determine the wave number of acrylate emulsions obtained.